Faktor yang mempengaruhi Keputusan dalam Membeli Rumah Ditinjau dari Perspektif Konsumen - Endang Prihatiningsih; Andi Mursalim; Simunawir Sitoro; Muhammad Nasir; Ratna Duwi Novita Lestari (Universitas Batanghari Jambi, 2023)
Home as a place to live is one of the basic human needs along with eating and drinking. Therefore, individuals need different options and considerations when deciding to own their home as a long-term residence. The purpose of this work is to analyze the effect of price perception and location on the apartment purchase decisions of consumers in Tama City 4 Sangatta apartment. The research used a quantitative approach. 70 respondents who bought a house in Tama City 4 Sangatta apartment under study. The results of the analysis show that price perception affects the decision to buy an apartment in Tama City 4 Sangatta apartment. Location influences the decision to buy an apartment in Tama City 4 Sangatta Apartment. Price perception and location significantly influence the decision to buy an apartment in Tama City 4 Sangatta apartment.